2007
DOI: 10.1037/0022-0663.99.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Job resources boost work engagement, particularly when job demands are high.

Abstract: This study of 805 Finnish teachers working in elementary, secondary, and vocational schools tested 2 interaction hypotheses. On the basis of the job demands-resources model, the authors predicted that job resources act as buffers and diminish the negative relationship between pupil misbehavior and work engagement. In addition, using conservation of resources theory, the authors hypothesized that job resources particularly influence work engagement when teachers are confronted with high levels of pupil miscondu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

75
1,089
12
78

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 1,504 publications
(1,254 citation statements)
references
References 85 publications
(125 reference statements)
75
1,089
12
78
Order By: Relevance
“…These results are consistent with earlier research with health employees that revealed beneficial consequences of emotional demands at work when personal resources are available (Bakker-Sanz-Vergel, 2012;Bakker et al, 2007;De Jonge et al, 2008). The findings are also in line with the recent developments in occupational health psychology about the matching principle (De Jonge & Dormann, 2006), which predicts that high (but not overwhelming) job demands stimulate positive psychological or physiological states best as long as employees possess sufficient functional, corresponding kinds of resources.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with earlier research with health employees that revealed beneficial consequences of emotional demands at work when personal resources are available (Bakker-Sanz-Vergel, 2012;Bakker et al, 2007;De Jonge et al, 2008). The findings are also in line with the recent developments in occupational health psychology about the matching principle (De Jonge & Dormann, 2006), which predicts that high (but not overwhelming) job demands stimulate positive psychological or physiological states best as long as employees possess sufficient functional, corresponding kinds of resources.…”
Section: Discussionsupporting
confidence: 91%
“…In the past, emotional demands derived from caring for patients were normally associated with higher emotional exhaustion and stress (van den Tooren & De Jonge, 2008). However, emotional demands from nursing could also be a source of motivation, flourishing and challenge at the same time (Bakker at al., 2007;Bakker & Sanz-Vergel, 2013;De Jonge et al, 2008). Emotional work with patients is one of the inherent features of nursing work and probably one of the reasons for choosing and enjoying this profession (Morgan & Lynn, 2009;Sundin et al, 2007).…”
Section: Emotional Demands Motivation and Well-being In Nursing Profmentioning
confidence: 99%
See 1 more Smart Citation
“…In the health impairment process, job demands lead to strain in the form of emotional exhaustion (Schaufeli & Bakker, 2004), a core component of burnout which refers to feelings of being overextended and exhausted by one's work (Demerouti et al, 2001). The assumptions of the JD-R model have gained widespread empirical support (e.g., Bakker, Hakanen, Demerouti, & Xanthopoulou, 2007;Hakanen, Bakker, & Schaufeli, 2006).…”
Section: The Job Demands -Resources Modelmentioning
confidence: 99%
“…Las demandas laborales se refieren a los aspectos físicos y psicosociales de la organización que requieren un importante esfuerzo, y coste físico y psicológico (p. ej., emocional, cognitivo y conductual) por parte del trabajador 19 .…”
Section: Engagementunclassified